Investigation of Hopanoid Biomarkers in Lake Sediments by GC-MS and RP-HPLC-APCI-MS - Gamze Kavran Belin (E-Journal of Chemistry)
Hopanoids are mainly derived from bacteriohopanpolyols that occur especially in bacteria, show the importance of bacterial lipid contributions in geological materials. In this work, GC-MS and RP-HPLC-APCI-MS analyses of hopanoid biomarkers in oxic and anoxic sediment samples from Lake Cadagno (Swiss Alps) and Lake Voua de la Motte (Haute Savoie, France) are presented and discussed. Samples were ultrasonically extracted, fractionated by flush chromatography on silica gel and derivatised before the analyses. Periodic acid/ sodium borohydride cleavage was used to identify highly functionalised hopanoids